Quantitative and Qualitative Assessment of Verbal Fluency in Amnestic Mild Cognitive Impairment - Tuğçe Çabuk; Şükrü Torun; Demet Özbabalık Adapınar (Türk Nöroloji Dergisi, 2020)
Objective: The objective of this research was to compare the verbal fluency skills of patients diagnosed as having amnestic mild cognitive impairment (aMCI) with the participants without neurologic or psychiatric problems through quantitative and qualitative analysis, and to determine in which aspects patients with aMCI differed from the control group. Materials and Methods: The sample of this study consisted of 20 individuals who presented to Özel Acıbadem Eskisehir Hospital with the symptom of forgetfulness and were diagnosed as having aMCI, and a healthy control group of the same size (n=20). All participants were administered preplanned verbal fluency tests that are valid and reliable, specifically for the mother language. Intergroup comparisons were made in the light of quantitative and qualitative assessments. Through the quantitative analysis, the total number of words produced in a limited amount of time under certain conditions was evaluated, and through the qualitative analysis, clustering and switching skills and error patterns such as perseveration and category violation were assessed. Results: It was determined that the aMCI group showed a deterioration in verbal fluency skills, and individuals with aMCI had significantly lower scores on both phonemic (u=296.5, p<0.05) and semantic (u=296, p<0.05) verbal fluency tests when compared with the control group. In terms of the clustering extent and category violation, there was no significant difference between the groups in both phonemic and semantic categories (p>0.05 for all comparisons). In phonemic verbal fluency tests, word switching skills of the patient group were significantly lower than those of the control group (u=279, p<0.05). In the semantic fluency test, the perseveration ratio was significantly higher in the aMCI group than in the control group (u=96.5, p<0.05). Conclusion: The results support the view that verbal fluency tests are one of the effective ways of distinguishing a healthy old-aged individual from an individual with aMCI.